Reconsidering cotton pest management in West Africa - (:unkn) unknown (My University, 2019)
Insect pests represent a major constraint to the increase of cotton yield in West Africa. The cotton value chain has been involved to varying degrees in integrated pest management approaches (IPM) to reduce the use of insecticides and to limit health and environmental risks. However, a fundamental change in farming practices, oriented toward the stimulation of natural pest control services, is needed to invent more pesticide-efficient and resilient production systems. The levers for promoting natural pest regulation are multiple and actionable at different scales from field to territory, but still require deepening our knowledge of the life system of pests and their natural enemies. They also necessitate to better take into account the perception and practices of stakeholders, in a participatory approach of the collective management of resources and processes of innovation. Ultimately, the aim is to build a territorialized organization of individual and collective actions for the management of pests and ecosystem services, including ecological, economic and social dimensions.
Keywords: African Research